(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
Natural events and human activities are believed to be contributing to an increase in average global temperatures. Climate change has become a global concern, and its impact has continued to affect and threaten human life and, to a large extent, and the livelihood of most people across the globe. The study examined climate change and building sustainability in Nigeria, its implications, and the way forward. The paper focused on the implications of climate change on buildings, the economic impacts of climate change in Nigeria, and strategies to mitigate climate change impacts on buildings. The study also revealed that Buildings contribute significantly to climatic changes and their impacts on the natural environment. Sustainable buildings can reduce greenhouse gas emissions, minimize energy consumption, conserve water resources, and enhance resilience to climate-related risks. On this basis, the study concluded that the issue of climate change and building sustainability has significant implications for the environment, society, and economy. Nigeria, like any other country is experiencing the adverse effects of climate change, including increased temperatures, extreme weather events, and rising sea levels. These impacts pose a threat to human health, livelihoods, and infrastructure. Addressing climate change through building sustainability in Nigeria requires a multi-faceted approach involving awareness, policy, finance, collaboration, research, and community engagement. One of the recommendations made was that there is a need for increased awareness and education about the importance of sustainable buildings and their role in climate change mitigation and adaptation. This can be done through public campaigns, training programs, and educational initiatives targeting architects, engineers, policymakers, and the general public.